(untitled) (Damascus University Journal of arts and humanities sciences, 2024)
The researcher aimed to determine the degree of awareness among Syrian youth about digital drugs music, in addition to monitoring the degree to which they listen to it, and identifying differences in the degree of awareness according to demographic variables (gender, age, and economic and social level). The study relied on the survey method, and its tool was the questionnaire that was distributed to an available sample of (207) individuals, and the researcher reached several results, the most important of which are: The degree of awareness among the sample members about digital drug music is medium at a rate of (50.7%), and the degree of their listening to this music is low at a rate of (52.8%), with non-statistically significant differences in the degree of awareness depending on demographic variables (gender, age, and economic and social level).